Tinjauan Fiqih Siyasah Terhadap Keputusan Walikota Medan No. 800/613k tentang Pemberhentian Aparatur Sipil Negara - Zaini, Muhammad Fahru; Sari, Seva Maya (MUKADIMAH: Jurnal Pendidikan, Sejarah, dan Ilmu-ilmu Sosial, 2025)
This study examines the Mayor of Medan’s Decree No. 800/613k regarding the dismissal of a civil servant (ASN) named Wan Muhammad Rizki, through the lens of fiqh siyasah (Islamic political jurisprudence). The decision was based on a criminal conviction that had reached legal finality in 2014, despite the fact that the individual had served his sentence, resumed his duties in 2015, and received several performance awards until 2018. The central issue in this research is the extent to which the dismissal aligns with the principles of justice, public interest (maslahah), and proportionality as outlined in fiqh siyasah. This study employs a qualitative method with a normative-juridical approach and descriptive analysis. The findings indicate that the dismissal may overlook the principles of rehabilitation and substantive justice recognized within fiqh siyasah, as it fails to consider the individual’s post-conviction contributions and positive professional record. The study concludes by emphasizing the importance of integrating positive legal norms with the ethical framework of Islamic leadership in public policymaking, particularly when dealing with individuals who have undergone penal processes and demonstrated moral recovery and professional competence.